Ultra-small curcumin-ruthenium coordination polymer nanodots prevent renal ischemia-reperfusion injury and the progression to chronic kidney disease - Liu, Xian; Yu, Qin; Mao, Hai-Bo; Hu, Jing-Bo; Liu, Wei-Hua (Frontiers in Bioengineering and Biotechnology, 2025)
Renal ischemia-reperfusion (IR) induces tissue hypoxia, resulting in disrupted energy metabolism and heightened oxidative stress. These factors contribute to tubular cell damage, which is a leading cause of acute kidney injury (AKI) and can progress to chronic kidney disease (CKD). The excessive generation of reactive oxygen species (ROS) plays a crucial role in the pathogenesis of AKI. This study presents the synthesis of curcumin ultra-small coordination polymer (Ru/Cur) nanodots and their application in scavenging ROS in renal tissues. By adding ruthenium ions to a methanol solution containing the natural product curcumin, ultra-small Ru/Cur nanodots were successfully synthesized. To enhance the dispersibility of these nanoparticles in water, polyvinylpyrrolidone (PVP) was used as a growth aid, resulting in highly stable nanodots with sizes smaller than 10 nm. The results indicated that Ru/Cur nanodots effectively eliminated various ROS and demonstrated significant therapeutic effects and biocompatibility in IR-AKI mice, reducing markers of kidney function damage, alleviating renal oxidative stress, and decreasing inflammatory cell infiltration. Ru/Cur nanodots inhibited renal fibrosis by suppressing epithelial-mesenchymal transition and the secretion of transforming growth factor-β1 in the model of IR-AKI to chronic kidney disease (CKD). In summary, our findings confirm that Ru/Cur nanodots mitigate the pathological conditions associated with both AKI and its progression to CKD by reducing IR-induced tubular cell injury.